The hasheesh eater : being passages from the life of a Pythagorean - Ludlow, Fitz Hugh, 1836-1870 (Subterranean lives., 2006)
Fitz Hugh Ludlow was a recent graduate of Union College in Schenectady, New York, when he vividly recorded his hasheesh-induced visions, experiences, adventures, and insights. During the mid-nineteenth century, the drug was a legal remedy for lockjaw, and Ludlow had a friend from whom he received a ready supply. He consumed such large quantities at each sitting that his hallucinations have been likened to those experienced by opium addicts. Throughout the book, Ludlow colorfully describes his psychedelic journey that led to extended reflections on religion, philosophy, medicine, and culture. F.